Research on the optimization of welding parameters in high-frequency induction welding pipeline. (November 2020) - Kang, Cunfeng; Shi, Chunyang; Liu, Zixiao; Liu, Zhifeng; Jiang, Xiaoqing; Chen, Shunjun; Ma, Chunmin
Abstract: In this paper, numerical simulation and finite element analysis were applied to optimize the important parameters including V-type joint and current frequency for high-frequency induction welding. The coupling of the 3D harmonic electromagnetic field and 3D transient temperature field was analyzed by establishing the physical file of the electromagnetic field and temperature field in high-frequency induction welding. The influence of important welding parameters on the temperature field distribution in the welding area was obtained by using a single control variable method. In the temperature field, the size of the V-type joint determines the heating efficiency, and the current frequency affects the heat produced by the eddy current. The numerical simulation results were verified by the analysis of the actual production experimental results and a good process parameter group was summarized. The shape of the slit between the different V-type joint parameters and the centerline of the squeeze roll showed that the relationship of the welding image and the welding quality and provided a solution for real-time online monitoring of welding quality.